A Review Study on The Practice of Enhancing Motivation of Students in Learning Mathematics - Bista, Padam (Okhaldhunga Journal, 2024)
Students' involvement and success in mathematics are greatly influenced by their motivation. Students that are motivated are more likely to actively participate in the learning process by contributing to class discussions, posing inquiries, and looking for answers to issues. This study is based on the review of articles and journals related to the practice of enhancing motivation of students in learning mathematics. The study finds efficient tactics, interventions, and methods that have been used to boost motivation in mathematics instruction by reviewing the body of existing literature on the subject. The review study's findings give educators, researchers, and decision-makers important information about how to create and carry out interventions that boost students' motivation and enhance their mathematics learning outcomes.